The impact of integrated information systems on management accounting : case of Croatia - Pervan, Ivica, ekonomist (Array, 2019)
The main aim of this study is to analyze how implementation of integrated information systems (IIS) effects management accounting. Findings based on data collected from 108 Croatian firms confirmed that IIS implementation caused significant management accounting changes. Estimated regression models revealed that the most important IIS characteristic were the analytical capabilities since it positively influenced management accounting changes in four dimensions: internal reporting, budgeting, application of modern accounting techniques and management accounting employees’ jobs. The quality of IIS implementation statistically significantly and positively influenced changes related to data collection and internal reporting. In the segment of budgeting, the quality of implementation of specialized budgeting software had significant and positive influence. The only negative correlation found was the one between the uncertainty of business environment and adoption of modern accounting techniques. Findings from this study provide unique insight into effects of IIS implementation in Croatian firms and can be used by different stakeholders. Firms and IIS vendors should put special focus on implementation of business analytics modules in order to achieve comprehensive benefits in management accounting practices. Providers of accountant’s education should consider the fact that contemporary IIS systems’ environment calls for development of additional skills in the area of information technology, business processes and business communication.